Pandanipora fragilis—a new deep-water cyclostome bryozoan from the subequatorial Mid-Atlantic Ridge, Atlantic Ocean, and a review of Pandanipora worldwide - Grischenko, Andrei V.; Gordon, Dennis P.; Melnik, Viacheslav P. (Zootaxa, 2020)
A new cyclostome bryozoan, Pandanipora fragilis n. sp., is described from 3453 m depth on the subequatorial Mid-Atlantic Ridge. It differs from the type species, P. helix Grischenko, Gordon & Melnik, 2018, by a combination of colonial and zooidal characters. These include regular branching of a uniserial stem along the entire colony length; a straight or just slightly elevated and gently curved distal autozooidal peristomial component, forming a sharp angle with the frontal wall of the next zooid; the pattern of zooidal budding, achieved via development of a partition from the floor of the parent zooid in its distal quarter to third, leaving the proximal portion of daughter zooids not overlapping, so that preceding and subsequent zooids are not appressed along their proximal segments; props are uniformly straight and filiform, with their diameter much smaller than in P. helix; the exceptionally rare presence of slit-like pseudopores, restricted to props; and wedge-shaped crystallites on the internal surface of developing zooids, with irregular, ragged edges. The discovery of P. fragilis suggests that Pandanipora is most likely a relict element of a more-widespread ancient distribution that existed in tropical and boreal zones of both the Atlantic and Pacific Oceans prior to formation of the Isthmus of Panama in the Pliocene.